Reduced Risk of Catastrophic Optical Mirror Damage in High Power Tapered Lasers using Intra-Cavity Divering Lens - TEE, Chyng Wen (Institutional Knowledge at Singapore Management University, 2006)
This paper approaches the problem of catastrophic optical mirror damage from a geometrical waveguide point of view. Instead of engineering the characteristics of the semiconductor material at the facet of the laser using quantum-well intermixing or other sophisticated wafer growth technique, a simple intra-cavity diverging lens concept is proposed and demonstrated to be capable of effectively expanding the lateral optical mode in order to counter the effect of SHB and thermal lensing effect, thereby reducing the risk of COMD. The Gaussian output beam profile is maintained throughout the whole of the current range tested, showing that expanding the nearfield at facet using integrated lens does not compromise the brightness of the laser. A key finding in this work is that the diverging effect on an optical mode is a thoroughly scalable effect that can be engineered by varying the etch-depth of the integrated lens. Fabrication of the lens is compatible with existing laser manufacturing process flow in that it can be easily implemented either by post-processing technology or by an additional lithographical step. This opens up new possibility in device design, with the beam width along the lateral direction being a parameter that can be optimized in isolation.